2018
DOI: 10.5530/pj.2018.2.56
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacognostic Evaluation of Curcumin on Diabetic Retinopathy in Alloxan-induced Diabetes through NF-KB and Brn3a Related Mechanism

Abstract: Background: Diabetic retinopathy is one of the most common micro vascular complication of diabetes and involves an abnormal pathology of major retinal pigment epithelium, inter retinal oedema and intraocular neovascularisation where pro-inflammatory proteins including ICAM-1,iNOS and VEGF release by activation of enzyme CaMKII/NF-kB expression Diabetic induced oxidative stress followed by deactivation of Brn3a expression in the retinal ganglionic cells are also early events in pathogenesis of Diabetic retinopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…In a previous study, following treatment with curcumin, a significant reduction in the thickness of the retinal capillary basement membrane was observed in diabetic rats treated with curcumin, but not in the untreated diabetic rats ( 70 ). Some scholars have confirmed that curcumin can reduce the expression of VEGF, inducible nitric oxide synthase (iNOS) and ICAM-1 by inhibiting the activation of CaMKII/NF-κB signaling in the diabetic rat retina and in Müller cells cultured in high glucose ( 71 , 72 ). Curcumin not only exerts anti-VEGF effects on the retina, but also exerts anti-angiogenetic effects on the choroidal vascular system of diabetic rats.…”
Section: Protective Effects Of Curcumin On Drmentioning
confidence: 99%
“…In a previous study, following treatment with curcumin, a significant reduction in the thickness of the retinal capillary basement membrane was observed in diabetic rats treated with curcumin, but not in the untreated diabetic rats ( 70 ). Some scholars have confirmed that curcumin can reduce the expression of VEGF, inducible nitric oxide synthase (iNOS) and ICAM-1 by inhibiting the activation of CaMKII/NF-κB signaling in the diabetic rat retina and in Müller cells cultured in high glucose ( 71 , 72 ). Curcumin not only exerts anti-VEGF effects on the retina, but also exerts anti-angiogenetic effects on the choroidal vascular system of diabetic rats.…”
Section: Protective Effects Of Curcumin On Drmentioning
confidence: 99%
“…Curcumin also reduces retinal diabetic damage in diabetic rats through inactivation of NF-κB and a decrease in IL-1β levels [38]. There is some indication that curcumin may influence NF-κB by preventing the diabetes-induced retinal activation of calcium/calmodulin-dependent protein kinase II (CAMKII) [27,74,75,76], a ubiquitous multifunctional protein kinase implicated in the regulation of the transcriptional activity of NF-κB [77]. Curcumin has also been observed to reverse the diabetes-induced upregulation of retinal GFAP in Müller cells of STZ rats [36].…”
Section: Nutraceuticals and Inflammationmentioning
confidence: 99%
“…In HG-induced ARPE-19 cells, curcumin treatment significantly reduced ROS production [ 12 ]. Consumption of curcumin in alloxan-induced DR rats increased the number of retinal ganglion cells under oxidative stress by increasing Brn3a expression [ 56 ]. Docosahexanoic acid (DHA) is a polyunsaturated fatty acid that is synthesized from the plant linolenic acid's fatty acid and is essential for the growth and development of the brain and retina that is also beneficial for pregnancy and lactation [ 57 , 58 ].…”
Section: Antioxidant Phytochemicals Against Drmentioning
confidence: 99%